Clinical and immunological profile of pediatric HIV infection in Ibadan, Nigeria (2011)
In spite of the increasing number of children living with HIV in Nigeria, published data on their clinical profile are few. We describe the clinical profile at presentation of HIV-infected children at the University College Hospital, Ibadan, in a prospective study. Among 272 children studied (149 [54.8%] males; mean age 4.2 years [range 2 months to 15 years]), infection was acquired through vertical transmission in 252 (92.6%), blood transfusion in 5 (1.80%), and undetermined routes in 15 (5.5%) cases. Clinical features included weight loss (62.5%), prolonged fever (55.4%), generalized lymphadenopathy (48.6%), chronic cough (45.4%), and persistent diarrhea (28.3%). Tuberculosis was present in 45.3%, World Health Organization (WHO) clinical stages 3 and 4 disease in 70.6% and severe immunosuppression in 44.5% of cases. Pediatric HIV in Ibadan is acquired mainly vertically and most cases present with severe disease. Improved access to prevention services and early diagnosis are recommended.